The CUL3–KLHL3 E3 ligase complex mutated in Gordon's hypertension syndrome interacts with and ubiquitylates WNK isoforms: disease-causing mutations in KLHL3 and WNK4 disrupt interaction - Ohta, Akihito (Portland Press Ltd., 2013)
The WNK (with no lysine kinase)–SPAK (SPS1-related proline/alanine-rich kinase)/OSR1 (oxidative stress-responsive kinase 1) signalling pathway plays an important role in controlling mammalian blood pressure by modulating the activity of ion co-transporters in the kidney. Recent studies have identified Gordon's hypertension syndrome patients with mutations in either CUL3 (Cullin-3) or the BTB protein KLHL3 (Kelch-like 3). CUL3 assembles with BTB proteins to form Cullin–RING E3 ubiquitin ligase complexes. To explore how a CUL3–KLHL3 complex might operate, we immunoprecipitated KLHL3 and found that it associated strongly with WNK isoforms and CUL3, but not with other components of the pathway [SPAK/OSR1 or NCC (Na(+)/Cl(−) co-transporter)/NKCC1 (Na(+)/K(+)/2Cl(−) co-transporter 1)]. Strikingly, 13 out of the 15 dominant KLHL3 disease mutations analysed inhibited binding to WNK1 or CUL3. The recombinant wild-type CUL3–KLHL3 E3 ligase complex, but not a disease-causing CUL3–KLHL3[R528H] mutant complex, ubiquitylated WNK1 in vitro. Moreover, siRNA (small interfering RNA)-mediated knockdown of CUL3 increased WNK1 protein levels and kinase activity in HeLa cells. We mapped the KLHL3 interaction site in WNK1 to a non-catalytic region (residues 479–667). Interestingly, the equivalent region in WNK4 encompasses residues that are mutated in Gordon's syndrome patients. Strikingly, we found that the Gordon's disease-causing WNK4[E562K] and WNK4[Q565E] mutations, as well as the equivalent mutation in the WNK1[479–667] fragment, abolished the ability to interact with KLHL3. These results suggest that the CUL3–KLHL3 E3 ligase complex regulates blood pressure via its ability to interact with and ubiquitylate WNK isoforms. The findings of the present study also emphasize that the missense mutations in WNK4 that cause Gordon's syndrome strongly inhibit interaction with KLHL3. This could elevate blood pressure by increasing the expression of WNK4 thereby stimulating inappropriate salt retention in the kidney by promoting activation of the NCC/NKCC2 ion co-transporters. The present study reveals how mutations that disrupt the ability of an E3 ligase to interact with and ubiquitylate a critical cellular substrate such as WNK isoforms can trigger a chronic disease such as hypertension.